Effect of schistosomiasis on CX3CR1‐expressing mononuclear phagocytes in the ileum and mesenteric lymph nodes of the mouse. Issue 11 (24th August 2015) - Alpaerts, K.; Buckinx, R.; Cools, N.; Heylen, M.; Nullens, S.; Berneman, Z.; De Winter, B.; Adriaensen, D.; Van Nassauw, L.; Timmermans, J.‐P.
Abstract Background Intestinal dendritic cells (DCs) maintain immune homeostasis, only initiating an active immune response against invading pathogens. However, little information is available on the reaction of mononuclear phagocytes (MNP) to intestinal trematode infection, a reaction equally important in helminth‐based therapies. The CD11c+ CX3CR1+ F4/80− DCs in the ileal lamina propria (LP) of the mouse were proven to migrate to the mesenteric lymph nodes (MLNs). We analyzed all MNP subsets present in the mouse LP and MLNs, under steady‐state conditions and during acute Schistosoma mansoni‐induced inflammation. Furthermore, we studied the uptake of schistosomal antigens by MNP in vivo in the LP and MLNs. Methods Using a combination of immunohistochemistry and multiparametric flow cytometry, we investigated distributional changes of the MNP during acute intestinal schistosomiasis. Next, S. mansoni‐derived products, i.e., S. mansoni soluble worm proteins (SmSWP) and S. mansoni soluble egg antigens (SmSEA) were intraperitoneally injected into CX3CR1+/GFP C57BL/6 mice and antigen uptake was analyzed using confocal microscopy. Key Results The CD11c+ CX3CR1+ F4/80− DCs significantly increased during intestinal schistosomiasis in the LP and MLNs. Only CX3CR1‐expressing DC and MФ subsets, but not other LP DCs, are involved in both SmSWP and SmSEA antigen uptake and processing. Conclusions & inferences The significant upregulation of CD11c+ CX3CR1+ F4/80− DCs during intestinal schistosomiasis and the restriction of phagocytosis of parasitic antigens to CX3CR1‐expresssing MNP indicate a crucial role for this immune cell niche in response to trematodiasis. These findings add insight into the functional specialization of LP immune cells and add to the understanding of cellular mechanisms behind helminth‐based therapies.